Nuclear Waste Land. - Fairley, Peter
The nuclear power industry needs a coherent plan for dealing with its reactors' radioactive and toxic leftovers. Burying the waste is a slow, politically painful process that leaves much to be desired. Lately, nuclear advocates, particularly in the United States, say they've found a better solution, or at least a path to one. It's based on the recycling and reuse of spent nuclear fuel, known as fuel reprocessing in the industry's jargon. Reprocessing breaks down fuel chemically, recovering fissionable material for use in new fuels. Thus, there is less highly radioactive material that needs to be sealed in caskets, buried deep underground, or otherwise permanently isolated from humankind. An ideal test case to evaluate fuel reprocessing is France, which never backed away from nuclear energy and which has long relied on reprocessing as the linchpin of its power reactor fuel system. The French experience clearly does show that reprocessing need not be the dangerous mess that other countries, including the United States
Keywords: Fissionable material; Fuel reprocessing; Nuclear fuel recycling; Nuclear power industry; Nuclear reactor; Power reactor fuel system; Radioactive material